The purposes of this research were, (1) to analyze fiscal policy impact on food security performance and (2) to determine strategic policy on food security in North Sumatera Province. Model of fiscal policy in North Sumatera Province which was built with the dynamic simultaneous equations system and used 2SLS with SYSLIN and SIMNLIN procedures. In this study we also used pooled data in 1990-2007 period. The results of this study showed that (1) factors of fiscal performance in North Sumatera - Boyke T. H. Situmorang; Harianto .; Mangara Tambunan; Nunung Kusnadi (Forum Pasca Sarjana, 2010)
The purposes of this research were, (1) to analyze fiscal policy impact on food security performance and (2) to determine strategic policy on food security in North Sumatera Province. Model of fiscal policy in North Sumatera Province which was built with the dynamic simultaneous equations system and used 2SLS with SYSLIN and SIMNLIN procedures. In this study we also used pooled data in 1990-2007 period. The results of this study showed that (1) factors of fiscal performance in North Sumatera, i.e. local tax and tax sharing were influenced by local GDP positively, otherwise general alocation funds and local retribution were not influenced by local GDP; (2) during fiscal policy, food security performance increased, which was interpreted with increasing on live expectation age, decreasing infant mortality number, and malnutrition number; (3) in simulation section, decreasing of illiteracy and health expenditure gave better impact on food security and also increasing local GDP than other simulation. Fiscal policy, especially in health and education sector, will stimulate quality social life in the future. Key words: local fiscal policy, food security, simultaneous equations